Effects of tetracycline and clotrimazole ointments in the treatment of palmar arsenical keratosis - Asiya Ferdous; Mir Misbahuddin; Abu Naser Ibne Sattar (Bangladesh Pharmacological Society, 2020)
The study was designed to see the effects of tetracycline and clotrimazole on the altered skin flora (Aspergillus and Enterobacter species) in 38 patients with palmar arsenical keratosis. The skin swab and scrapping samples were collected. Tetracycline, clotrimazole and their combination were given as ointment for 3 months. Clotrimazole and tetracycline were found to inhibit the growth of Aspergillus spp. and Enterobacter spp. in vitro. A pH-dependent inhibition of the growth of microorganisms in presence of these antimicrobials was observed, which was highest at pH 8. The percentage reduction of keratotic nodular size was 32.9, 66.1, 61.1 and 32.5 in the groups treated with placebo, tetracycline, clotrimazole and the combination of both, respectively. But none of the interventions was proved statistically significant. No remarkable adverse effect was reported. In conclusion, clotrimazole or tetracycline inhibits the growth of Aspergillus spp. or Enterobacter spp. in vitro. However, there was no statistically significant clinical improvement of the palmar arsenical keratosis.